Efektivitas Corporate Governance dan Fraudulent Financial Reporting - Kusumawardani, Media; Soediro, Achmad; Adhitama, Fardinant; Farhan, Muhammad (E-Jurnal Akuntansi; Vol 33 No 5 (2023)DO - 10.24843/EJA.2023.v33.i05.p11, 2023)
This study aims to examine the role of corporate governance on fraudulent financial reporting. Research with the variables used is rarely studied, especially regarding the skills of the board of commissioners, the number of meetings and the role of women. The research sample is 469 manufacturing companies. Tests were carried out using logistic regression using the SPSS application which tested corporate governance variables represented through the role of the board of commissioners from the point of view of size, independence, expertise, meet, gender diversity towards fraudulent financial reporting. The results of the study show that the board of commissioners (size) and the board of commissioners (gender diversity) have a negative effect on fraudulent financial reporting. Another independence variable, namely the board of commissioners (independence, expertise, meet) is not proven to have an effect on fraudulent financial reporting. Keywords: The Board of Commissioner (Size, Independensi, Expertise, Meet, Gender); Fraudulent Financial Reporting